Fermented black soldier fly (Hermetia illucens) carcass meal as a substrate for its larva - PIERE ALEXANDER HUGO RIOK; NOVA HARIANI; RUDY AGUNG NUGROHO; MUHAMMAD FAUZI ARIF; SYAFRIZAL SYAFRIZAL; RETNO ARYANI; HETTY MANURUNG; RUDIANTO RUDIANTO (Nusantara Bioscience, 2025)
Abstract. Riok PAH, Hariani N, Nugroho RA, Arif MF, Syafrizal, Aryani R, Manurung H, Rudianto. 2025. Fermented black soldier fly (Hermetia illucens) carcass meal as a substrate for its larva. Nusantara Bioscience 17: 49-56. The black soldier fly (Hermetia illucens (Linnaeus, 1758)) is an insect commonly used as an organic waste decomposer. The Black Soldier Fly (BSF) has four life stages, and as an adult, it dies shortly after reproducing, which leads to it being an underutilized waste product. This study aimed to determine and compare the effects of the fermented BSF Carcass Meal (fBSFM) and Fermented Palm Kernel Meal (fPKM) as substrates on the growth rate and proximate composition of BSF Larvae (BSFL). The present research used a completely randomized design with four groups: a control group (100% fPKM) and three experimental groups with varying percentages of fBSFM (P1: 5% fBSFM, P2: 7.5% fBSFM, P3: 10% fBSFM). The results showed that substituting fBSFM at concentrations of 7.5- and 10% in fPKM increased growth rate, individual weight, biomass, and bioconversion, supporting their life cycle; the use of 15% fBSFM as BSFL substrate significantly impacted substrate reduction. The substrate reduction rate was measured at 55.18 ± 8.49%, suggesting that black soldier fly larvae can effectively reduce both fBSFM and fPKM. The different proportions of fPKM and fBSFM did not have a significant effect on the proximate values of the BSFL. Therefore, this research provides valuable insight for waste management and agriculture, suggesting that incorporating more than 5% of fermented BSF carcass meal into the substrate mixture with fPKM is advisable to enhance the growth indices of BSFL.